2012
DOI: 10.5194/acp-12-2567-2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of observed and modeled OH and HO<sub>2</sub> concentrations during the ambient measurement period of the HO<sub>x</sub>Comp field campaign

Abstract: Abstract. A photochemical box model constrained by ancillary observations was used to simulate OH and HO2 concentrations for three days of ambient observations during the HOxComp field campaign held in Jülich, Germany in July 2005. Daytime OH levels observed by four instruments were fairly well reproduced to within 33% by a base model run (Regional Atmospheric Chemistry Mechanism with updated isoprene chemistry adapted from Master Chemical Mechanism ver. 3.1) with high R2 values (0.72–0.97) over a rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 50 publications
6
27
2
Order By: Relevance
“…Using the fast isomerization rates calculated by Peeters et al (2009) and Peeters and Müller (2010), the box model calculated HO 2 mixing ratios which are up to 3 times greater than the HO 2 measurements (Fig. S3 in the Supplement), consistent with recent model-to-observation comparisons in other forest studies (Kanaya et al, 2012;Lu et al, 2011;Whalley et al, 2011). However, when the isomerization rate is reduced for the unimolecular isomerization channel in accordance with recent laboratory studies , the HO 2 from the Peeters mechanism comes into better agreement with the HO 2 measurements (Fig.…”
Section: Temperature Dependencesupporting
confidence: 82%
“…Using the fast isomerization rates calculated by Peeters et al (2009) and Peeters and Müller (2010), the box model calculated HO 2 mixing ratios which are up to 3 times greater than the HO 2 measurements (Fig. S3 in the Supplement), consistent with recent model-to-observation comparisons in other forest studies (Kanaya et al, 2012;Lu et al, 2011;Whalley et al, 2011). However, when the isomerization rate is reduced for the unimolecular isomerization channel in accordance with recent laboratory studies , the HO 2 from the Peeters mechanism comes into better agreement with the HO 2 measurements (Fig.…”
Section: Temperature Dependencesupporting
confidence: 82%
“…Studies of ambient HO x during the field campaign HOx-Comp2005 in Jülich have shown relatively good agreement (within 30 %) between modelled and measured OH Kanaya et al, 2012). Interestingly, agreement was found both for high and low NO concentrations, contrasting the PRD and Yufa results where significant OH discrepancies were found at similar isoprene concentrations at low NO.…”
Section: Further Discussionmentioning
confidence: 95%
“…It has been speculated that the missing recycling is related to isoprene (e.g. Lelieveld et al, 2008;Ren et al, 2008;Paulot et al, 2009;Peeters et al, 2009;Peeters and Müller, 2010;Whalley et al, 2011;Lu et al, 2012), but a consistent chemical mechanism explaining the measured concentrations of both OH and HO 2 has not been identified so far (Crounse et al, 2011;Whalley et al, 2011;Lu et al, 2012;Kanaya et al, 2012).…”
mentioning
confidence: 99%
“…96 M. M. Lew et al: Hydroperoxy radical in the atmosphere using laser-induced fluorescence 2009b; Michoud et al, 2012;Lu et al, 2013;Ren et al, 2013;Griffith et al, 2016), while other times the measurements were found to be both lower (George et al, 1999;Konrad et al, 2003) and higher than model predictions Ren et al, 2003;Emmerson et al, 2005;Kanaya et al, 2007a;Chen et al, 2010;Sheehy et al, 2010;Czader et al, 2013;Griffith et al, 2016). In forested environments, measured HO 2 concentrations were sometimes found to agree with model predictions (Tan et al, 2001;Ren et al, 2005Ren et al, , 2006 but were often found to be either lower (Carslaw et al, 2001;Kanaya et al, 2007bKanaya et al, , 2012Whalley et al, 2011;Mao et al, 2012;Griffith et al, 2013) or higher than model predictions (Carslaw et al, 2001;Kubistin et al, 2010;Kim et al, 2013;Hens et al, 2014).…”
Section: Introductionmentioning
confidence: 87%